2021
DOI: 10.1002/pc.26227
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional nickel‐coated carbon fiber veil for improving both fracture toughness and electrical performance of carbon fiber/epoxy composite laminates

Abstract: The poor lightning strike resistance limits the application of carbon fiberreinforced polymer (CFRP) composites in aircraft. Multifunctional fiber composites can reduce lightning strike damage by improving interlaminar mechanical properties and electrical conductivity. In this study, nickel-coated carbon fiber (NiCF) veil was explored as a functional interleaf of CFRP composites to simultaneously improve the interlaminar fracture toughness (G IC by 74.75% and G IIC by 36.22%) and through-thickness electrical c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 40 publications
0
25
0
Order By: Relevance
“…The SEM images of both the veils are shown in Figure 1. Some nickel particles can be seen (highlighted with red arrows in Figure 1b) adhering to the fiber surface 40 . The random orientation of the veil fibers forms a uniform porous network structure, which aids in resin impregnation.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The SEM images of both the veils are shown in Figure 1. Some nickel particles can be seen (highlighted with red arrows in Figure 1b) adhering to the fiber surface 40 . The random orientation of the veil fibers forms a uniform porous network structure, which aids in resin impregnation.…”
Section: Methodsmentioning
confidence: 99%
“…Recently Liu et al 40 reported that a nickel‐coated carbon fiber (NiCF) veil improves the electrical conductivity and fracture toughness of carbon fiber/epoxy composites. The unidirectional carbon fiber/epoxy prepregs were used for manufacturing the laminates.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[9][10][11][12] Among them, the interlaminar toughening technique is a targeted and straightforward method to improve the IFT of composites. Simply laying a layer of toughening materials, which can be materials such as particles, [13] veils, [14][15][16][17][18][19][20] films, [21] electrospun nanofibers, [22,23] and fibers, [24] and so forth, at a specific location (usually the middlemost layer) can be a good way to improve the IFT. Short fibers, being widely available and having excellent mechanical properties, are often used to improve the interlaminar fracture toughness of composites.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] Nanoclays in conjunction with conductive fillers and nickel-coated fibers were used to increase the electrical conductivity of polymer composites. [9] Liu et al [10,11] incorporated nickel-coated carbon fiber veils in composite laminates, which improved the impact resistance and interlaminar fracture toughness (G IC , G IIC ), explained by additional energy dissipation through fiber pull-out breakage and peeling of the nickel coating. Ni-coated fiber composites have increased electromagnetic-wave absorptivity, which encourages their use in such applications as radar stealth, [12][13][14][15][16][17][18][19][20][21] interference shielding, [5] and microwave heating.…”
Section: Introductionmentioning
confidence: 99%